Intermittent Hypoxia Rewires the Liver Transcriptome and Fires up Fatty Acids Usage for Mitochondrial Respiration - Gaucher, Jonathan; Vial, Guillaume; Montellier, Emilie; Guellerin, Maëlle; Bouyon, Sophie; Lemarie, Emeline; Pelloux, Véronique; Bertrand, Anne; Pernet-Gallay, Karin; Lamarche, Frederic; Borel, Anne-Laure; Arnaud, Claire; et al. (Frontiers in Medicine, 2022)
Sleep Apnea Syndrome (SAS) is one of the most common chronic diseases, affecting nearly one billion people worldwide. The repetitive occurrence of abnormal respiratory events generates cyclical desaturation-reoxygenation sequences known as intermittent hypoxia (IH). Among SAS metabolic sequelae, it has been established by experimental and clinical studies that SAS is an independent risk factor for the development and progression of non-alcoholic fatty liver disease (NAFLD). The principal goal of this study was to decrypt the molecular mechanisms at the onset of IH-mediated liver injury. To address this question, we used a unique mouse model of SAS exposed to IH, employed unbiased high-throughput transcriptomics and computed network analysis. This led us to examine hepatic mitochondrial ultrastructure and function using electron microscopy, high-resolution respirometry and flux analysis in isolated mitochondria. Transcriptomics and network analysis revealed that IH reprograms Nuclear Respiratory Factor- (NRF-) dependent gene expression and showed that mitochondria play a central role. We thus demonstrated that IH boosts the oxidative capacity from fatty acids of liver mitochondria. Lastly, the unbalance between oxidative stress and antioxidant defense is tied to an increase in hepatic ROS production and DNA damage during IH. We provide a comprehensive analysis of liver metabolism during IH and reveal the key role of the mitochondria at the origin of development of liver disease. These findings contribute to the understanding of the mechanisms underlying NAFLD development and progression during SAS and provide a rationale for novel therapeutic targets and biomarker discovery.